Component Replacement Interval Policy based on Downtime Minimization using Age Repaclement Method: A Case Study of Autoclave-035 Machine - Redi Ahmad Putra Nuranto; Fransiskus Tatas Dwi Atmaji; Endang Budiasih (Peneliti.net, 2022)
PT XYZ is a pharmaceutical company located in West Bandung Regency. The company is engaged in the pharmaceutical sector and manufactures several products. One of the sub-units in this company is the Biological Product division which produces vaccines and sterilizes pharmaceutical equipment. In production activities in this sub-unit requires a steam engine to sterilize livestock machinery, the machine is called an Autoclave. The Autoclave-035 machine uses steam to sterilize so that viruses, bacteria, fungi, and other organisms can die. The Autoclave-035 machine often damage and malfunctions from 2019 to 2021 with 41 times of damage, causing engine downtime because it had not considered the service life of the engine components.. Therefore, it is necessary to analyze and design using the Age Replacement method to obtain the optimal component replacement time interval policy for Autoclave-35 machine. The results of this analysis are the Risk Priority Number values of the two most critical components, namely Drain Chamber and Door Seal. Then based on the Age Replacement model, the optimal service life of the Drain Chamber component is 16 years and the Door Seal is 18,2 years